Molluscan Check List of Ghodaghodi Tal Area, Kailali District - Subba, Bharat Raj (Our Nature, 2006)
The paper deals with ten freshwater and one terrestrial mollusc collected from Ghodaghodi Tal area. Among ten freshwater molluscs, nine species belong to six families viz. Planorbidae, Viviparidae, Pilidae, Lymnaedae and Thiaridae of class Gastropoda and one species is of family Amblemidae of the class Bivalvia. The single species of terrestrial mollusc belongs to family Ariophantidae of the class Gastropoda. Keywords: Molluscan diversity, Ghodaghodi Tal, Wetland doi:10.3126/on.v1i1.294 Our Nature (2003) 1: 1-2